Energy-saving fireproof durable copper alloy wire

By combining alumina-magnesium oxide-composite hemigel with hindered phenolic antioxidants in polyethylene wires, the problems of thermal aging and insufficient flame retardant properties of polyethylene wires are solved, and a longer-lasting antioxidant is achieved And flame retardant effects reduce costs and are suitable for industrial promotion.

CN119119610AInactive Publication Date: 2024-12-13HANGZHOU DIBO METAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229612.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyethylene wires are aging problems caused by environmental factors during long-term use, especially thermal aging. Existing antioxidants such as hindered phenols are prone to volatile, resulting in poor anti-aging effects and high cost of nanomaterials and difficult to promote.

Method used

Alumina-magnesium oxide-composite hexagonal gel is combined with hindered phenolic antioxidants, and composite oxidants are prepared through materials such as chitosan and aluminum chloride to form pore structures to adsorb and bind hindered phenolic antioxidants to reduce their Volatilize and combine aluminum hydroxide and magnesium hydroxide flame retardant to improve flame retardant performance.

Benefits of technology

It extends the validity period of antioxidants, improves the anti-thermal aging and flame retardant properties of wires, reduces costs, and makes it more valuable to promote and apply it in the industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005025689250000091
    Figure BDA0005025689250000091
  • Figure BDA0005025689250000092
    Figure BDA0005025689250000092
  • Figure BDA0005025689250000101
    Figure BDA0005025689250000101
Patent Text Reader

Abstract

The invention belongs to the technical field of wire manufacturing, and discloses an energy-saving fireproof durable copper alloy wire, which comprises a sheath and a conductor, and the sheath comprises the following components: 95-98 parts of polyethylene raw material; 1-3 parts of a composite antioxidant; 1-3 parts of a flame retardant; the composite oxidizing agent comprises aluminum oxide-magnesium oxide-composite xerogel and a hindered phenol antioxidant. The invention has the following effects: the hindered phenol antioxidant is small in molecular weight and easy to volatilize, so that the aluminum oxide-magnesium oxide-composite xerogel is researched and prepared, and the novel metal gel material has a pore structure and a large number of active groups, can adsorb, constrain and limit the volatilization of the hindered phenol antioxidant, and also has the advantages of low cost and high efficiency. The anti-oxidation effect of the hindered phenol antioxidant is not affected, volatilization of the hindered phenol antioxidant is effectively reduced when the electric wire works, especially works in a high-temperature environment, and the effects of aging resistance, durability, low manufacturing cost and industrial application and popularization value are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric wire manufacturing, and particularly relates to an energy-saving, fire-proof and durable copper alloy electric wire. Background Art

[0002] Wires and cables are basic products for transmitting electric energy and information, and are widely used in electric energy transmission, signal transmission and other purposes. The wire structure includes conductors and sheaths, of which the conductors are generally made of copper-aluminum alloys, and the sheath materials are generally made of polyethylene, polypropylene, polyvinyl chloride, silicone rubber and other materials. At present, polyethylene wires are the type with the largest output. The sheaths made of polyethylene have the advantages of stable chemical properties, good low temperature resistance, and resistance to corrosion by most acids and alkalis.

[0003] During the long-term use of polyethylene wires, the long-term effects of factors such as moisture in the environment, working temperature, and mechanical force will inevitably cause the sheath to age. The aged wires will easily cause insulation failure, power system and equipment failure. At present, the aging types of polyethylene sheaths are mainly divided into electrical aging, thermal aging, chemical aging, etc., among which thermal aging is the main one. In order to solve the aging problem of the sheath, antioxidants such as hindered phenols and phosphites are used in the prior art. For example, the Chinese invention patent application with application publication number CN118290841A discloses a high flame retardant and low smoke toxicity new energy cable, and the antioxidant used is a hindered phenol antioxidant.

[0004] Hindered phenol antioxidants are small molecule antioxidants. When the wires are used, especially when working at high temperatures, they are easily lost, resulting in unsatisfactory anti-aging effects. At present, there are many studies in the prior art that use nanomaterials to improve the anti-aging properties of polyethylene materials. Compared with hindered phenol antioxidants, nanomaterial antioxidants are not easy to lose and have better antioxidant properties. However, as a very mature basic product, the wire itself has very fierce market competition, especially price competition. Due to the high cost of nanomaterials, the use of nanomaterials as antioxidants is mostly limited to theoretical and experimental research, and it is difficult to promote large-scale application in the industry. Summary of the invention

[0005] The purpose of the present invention is to provide an energy-saving, fire-proof and durable copper alloy wire, which has the effects of anti-aging, durability, low manufacturing cost and industrial promotion and application value.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions: an energy-saving, fire-proof and durable copper alloy wire, including a sheath and a conductor. The sheath raw material includes the following components by weight: 95 to 98 parts of polyethylene raw material; 1 to 3 parts of composite antioxidant; 1 to 3 parts of flame retardant; the composite oxidant includes aluminum oxide-magnesium oxide-composite dry gel and hindered phenol antioxidant attached to the aluminum oxide-magnesium oxide-composite dry gel.

[0007] By adopting the above technical solution: hindered phenol antioxidants are phenolic compounds with a spatially hindered structure, and have the advantages of high antioxidant efficiency, stable chemical properties, and good light stability. Therefore, the present invention selects hindered phenol antioxidants to play a role in resisting thermal oxidative aging. However, hindered phenol antioxidants have a small molecular weight, and are easy to volatilize when working on wires, especially in high temperature environments.

[0008] Based on the above situation, the present invention has creatively researched and developed an aluminum oxide-magnesium oxide-composite dry gel, which is also an aerogel. The dry gel is solid on the outside and has a pore structure inside. The new metal gel material prepared by the present invention has a large number of pore structures and groups inside, which can provide attachment sites for hindered phenolic antioxidants. While not affecting the anti-thermal aging function of hindered phenolic antioxidants, it can restrain and limit the hindered phenolic antioxidants, effectively reducing the volatilization of hindered phenolic antioxidants.

[0009] The present invention is further configured as follows: the composite oxidant preparation method is as follows: aluminum chloride is added into an ethanol aqueous solution, and then mixed with chitosan sol, 1,2-propylene oxide and N,N-dimethylformamide are added, and ultrasonic treatment is performed after stirring evenly, and after the sol forms a gel, the formed gel is aged at room temperature and then added into anhydrous ethanol containing magnesium oxide powder, and stirred evenly and then allowed to stand at room temperature for 10 to 12 hours, and after the stirring and standing steps are repeated 3 to 5 times, a hindered phenol antioxidant is added and mixed evenly, and the composite oxidant is obtained after drying at 40 to 45°C.

[0010] By adopting the above technical solution, chitosan, also known as deacetylated chitosan, soluble chitosan, and polysaminoglucose, is a white powder, odorless and tasteless. The dissolved chitosan is in a gel state, contains a large number of groups such as hydroxyl and amino groups, and has good adsorption capacity.

[0011] The invention first prepares gel with aluminum chloride and chitosan sol, and then prepares composite oxidant with magnesium oxide and hindered phenol antioxidant. Chitosan sol and aluminum chloride solution first form chitosan-alumina composite, and then prepare composite dry gel. Magnesium oxide plays a role in improving the high temperature stability of dry gel material. In the composite oxidant, hindered phenol antioxidant is effectively adsorbed by the composite dry gel material, so that the volatilization of hindered phenol antioxidant can be effectively reduced, so that the heat aging resistance of the sheath is more durable and more durable.

[0012] The present invention is further configured as follows: in the preparation method of the composite antioxidant, a hindered phenol antioxidant is added while adding 1,2-propylene oxide and N,N-dimethylformamide, and then the mixture is stirred evenly and then subjected to ultrasonic treatment for 6 to 8 minutes.

[0013] By adopting the above technical solution, 1,2-propylene oxide is a gel accelerator, and N,N-dimethylformamide is a drying accelerator. Adding hindered phenolic antioxidants at the same time as adding 1,2-propylene oxide and N,N-dimethylformamide means that the hindered phenolic antioxidants are added twice. The hindered phenolic antioxidants added for the first time are bound and restricted more strongly. As the use time of the wires continues to increase, the hindered phenolic antioxidants added for the second time will inevitably have a small amount of loss. The hindered phenolic antioxidants added for the first time will gradually break free from the constraints and restrictions and play a greater role in resisting heat aging, playing a role of slow release, ensuring that the wires in long-term service still have good heat-oxidative aging resistance and ensuring the stability of the power system and power equipment.

[0014] The present invention is further configured as follows: by weight, 1 part of chitosan is dispersed in 30 parts of deionized water, and then acetic acid solution is added dropwise, and then stirred for 20 to 30 minutes to obtain chitosan sol.

[0015] By adopting the above technical solution, since chitosan is soluble in water and almost insoluble in ethanol, the present invention first disperses chitosan in deionized water, then drops acetic acid solution is added, and chitosan sol is obtained after stirring to prepare composite xerogel. It should be pointed out that the amount of acetic acid added needs to be added in an appropriate amount according to the actual situation, and it only needs to ensure that a light yellow chitosan sol can be obtained.

[0016] The present invention is further configured as follows: the mass ratio of chitosan, aluminum chloride, magnesium oxide and hindered phenol antioxidant in the chitosan sol is 1:4-8:3-6:4-8.

[0017] The present invention is further configured as follows: the polyethylene raw material includes LDPE and HDPE, and the mass ratio of LDPE to HDPE is 20:1.

[0018] By adopting the above technical solution, the polymer will crack when encountering an invasive environment, which is environmental stress cracking. Since the polyethylene material used in the wire sheath is to prevent the sheath from cracking in an invasive environment, it needs to have good environmental crack resistance.

[0019] Polyethylene is a polymer with high crystallinity, and it has both crystalline and amorphous structures. There are two types of connections between polyethylene crystal layers. One is the bridge-like tie molecule, whose two ends are connected to different crystal layers respectively, and the connection is achieved through intermolecular covalent bonds. The other is molecular chain entanglement. The bridge-like tie molecule is related to the molecular weight.

[0020] Firstly, HDPE is configured in the polyethylene raw material of the present invention, and the HDPE has a large molecular weight, which gives the polyethylene bridge-like tie molecules and improves the environmental crack resistance of the sheath. Secondly, chitosan is used in the alumina-magnesia-composite dry gel of the present invention. Chitosan contains a large number of groups such as hydroxyl groups and amino groups, which are easy to contact with polyethylene molecular chains, thereby increasing the resistance of the molecular chains of the polyethylene crystal layer to disentanglement, and can further improve the environmental crack resistance of the sheath, making the sheath material and the wire more durable.

[0021] The present invention is further configured as follows: the flame retardant is an aluminum hydroxide flame retardant and / or a magnesium hydroxide flame retardant.

[0022] By adopting the above technical solution, when short circuit, overload and other situations occur during the use of wires, it is easy to cause the wire sheath to overheat and burn, causing a fire. Fires caused by wires are common and can easily cause casualties and property losses. Therefore, wires need to have good flame retardant properties.

[0023] Sheath combustion is a complex physical and chemical process. When the sheath is overheated, its polymer material degrades, including thermal degradation and thermal oxidation degradation. Combustible gas is generated during the degradation process. The combustible gas diffuses into the gas phase and comes into contact with oxygen until the combustible gas reaches a combustible concentration and is exposed to a heat source. The combustible gas temperature rises above the critical combustion temperature, the combustible gas is ignited, and a large amount of heat is generated. Part of this heat diffuses into the surrounding environment, and part of it acts on the sheath, causing the sheath to continue to degrade, thereby continuously providing combustible gas.

[0024] The flame retardants selected in the present invention are aluminum hydroxide flame retardant and magnesium hydroxide flame retardant, both of which are low-smoke halogen-free flame retardants. Aluminum hydroxide flame retardant and magnesium hydroxide flame retardant are both metal flame retardants. When heated, they decompose to produce oxides and a large amount of water vapor. The water vapor dilutes the combustible gas and forms a gas isolation layer. The oxides produced by decomposition form a heat-insulating protective layer on the surface of the material, thereby playing a flame retardant role.

[0025] The uniqueness of the present invention lies in that, first, the composite dry gel contains oxides such as aluminum oxide and magnesium oxide, which can cooperate with the metal flame retardant to form an insulating protective layer when the sheath burns, thereby improving the flame retardant performance. Second, during the combustion of the sheath, the hindered phenol antioxidant is constrained and restricted and is not easy to volatilize, which can delay the thermal oxidation degradation process to a certain extent. Third, the composite dry gel has a low thermal conductivity and high high temperature stability, and can also play a certain flame retardant role.

[0026] The present invention is further configured as follows: the flame retardant includes an aluminum hydroxide flame retardant and a magnesium hydroxide flame retardant, and the mass ratio of the aluminum hydroxide flame retardant to the magnesium hydroxide flame retardant is 1:1.

[0027] By adopting the above technical solution, in order to improve the flame retardant effect of metal flame retardants, the existing technology generally adopts the ideas of surface modification, ultrafine method, synergistic flame retardancy, etc. Synergistic flame retardancy can be achieved by adding synergistic flame retardants and metal flame retardants cooperating with each other.

[0028] After research and taking into account the material of the composite dry gel, the present invention adopts a method of cooperating metal flame retardants to achieve synergistic flame retardancy. When the mass ratio of aluminum hydroxide flame retardant to aluminum hydroxide flame retardant is 1:1, the present invention can achieve a higher flame retardant effect.

[0029] The present invention is further configured as follows: the sheath preparation method is as follows: LDPE particles and HDPE particles are kneaded at 110° C. and a rotation speed of 80 r / min, and after melting, a composite antioxidant and a flame retardant are added and kneaded for 5 to 10 minutes, and then DCP is added and kneaded for 3 to 5 minutes, and then the sheath is extruded through a screw extruder to obtain the sheath.

[0030] The present invention is further configured as follows: the conductor comprises an inner core and a coating layer covering the inner core; the inner core is made of copper-aluminum alloy, and the coating layer is made of copper.

[0031] By adopting the above technical solution, the conductor adopts the coating and stretching process, and its inner core adopts 8030 aluminum alloy rod, which has better tensile resistance than ordinary aluminum rod. The outer layer is coated with copper to avoid the contact between aluminum and copper socket switch, which may cause oxidation of contact points and cause short circuit.

[0032] The beneficial effects of the present invention are: 1. The present invention uses hindered phenol antioxidants, which have the advantages of high antioxidant efficiency, stable chemical properties and good light stability. However, since hindered phenol antioxidants have a small molecular weight and are volatile, the present invention studies and prepares alumina-magnesium oxide-composite xerogels. This new metal gel material has a pore structure and a large number of active groups, which can adsorb, bind and restrict hindered phenol antioxidants while not affecting the antioxidant effect of hindered phenol antioxidants. It effectively reduces the volatilization of hindered phenol antioxidants when the wire is working, especially when working in a high temperature environment, and greatly overcomes the shortcoming of hindered phenol antioxidants being volatile.

[0033] 2. In the preparation process of the alumina-magnesia-composite xerogel of the present invention, the hindered phenolic antioxidant is added twice, and the restrictive effect of the alumina-magnesia-composite xerogel on the hindered phenolic antioxidant added for the first time is greater than the restrictive effect on the hindered phenolic antioxidant added for the second time. Therefore, when the hindered phenolic antioxidant added for the second time inevitably volatilizes during the long-term operation of the electric wire, the hindered phenolic antioxidant added for the first time can also play a role, and play a role of phased slow release, so as to ensure that the electric wire can have a high antioxidant performance during long-term service.

[0034] 3. The alumina-magnesium oxide-composite dry gel of the present invention has a porous structure, low thermal conductivity, and contains alumina and magnesium oxide. When the sheath burns, it can cooperate with the metal flame retardant to play a flame retardant role, which is beneficial to the formation of the metal oxide thermal insulation isolation layer, improves the flame retardant properties of the wire, and makes the wire more fireproof.

[0035] 4. The flame retardant in the sheath of the present invention is a low-smoke, halogen-free metal flame retardant. The synergistic flame retardancy is achieved through the coordination between the metal flame retardants, so that the sheath material has good flame retardant properties.

[0036] 5. The sheath material of the present invention can effectively improve the environmental cracking resistance of the sheath material through the ratio of LDPE and HDPE in the polyethylene raw material and the effect of alumina-magnesium oxide-composite dry gel, making the wire more durable and having a longer service life.

[0037] 6. Compared with antioxidants using nanomaterials, the raw materials of the sheath material of the present invention, such as chitosan, alumina, magnesium oxide, etc., are easy to obtain, have low cost, and are easier to apply and promote in the industry. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Embodiment 1: An energy-saving, fire-proof and durable copper alloy wire, comprising a conductor and a sheath. The conductor comprises an inner core and a sheath covering the inner core, the inner core is made of an aluminum alloy rod, and the sheath is made of copper. The conductor is prepared by a coating and stretching process. In terms of weight, the sheath raw material comprises the following components: 95 parts of polyethylene raw material; 1 part of composite antioxidant; 1 part of flame retardant; the composite oxidant comprises aluminum oxide-magnesium oxide-composite dry gel, and a hindered phenol antioxidant attached to the aluminum oxide-magnesium oxide-composite dry gel.

[0040] The polyethylene raw materials include LDPE, HDPE and DCP, and the mass ratio of LDPE to HDPE is 20:1. The flame retardants include aluminum hydroxide flame retardant and magnesium hydroxide flame retardant, and the mass ratio of aluminum hydroxide flame retardant to aluminum hydroxide flame retardant is 1:1. The content of DCP in the polyethylene raw material is 1.8phr.

[0041] The preparation method of the composite oxidant is as follows: 1 part of chitosan is dispersed in 30 parts of deionized water by weight, and then acetic acid solution is added dropwise, and then stirred for 20 minutes to obtain chitosan sol. Aluminum chloride is added to 45 parts of ethanol aqueous solution, and then mixed with chitosan sol, 1,2-propylene oxide, N,N-dimethylformamide, and hindered phenol antioxidant are added for the first time, stirred evenly, and then ultrasonic treatment is performed for 6 minutes. After the sol forms a gel, the formed gel is aged at room temperature and then added to anhydrous ethanol containing magnesium oxide powder, stirred evenly, and then allowed to stand at room temperature for 10 hours. After repeating the stirring and standing steps 3 times, the hindered phenol antioxidant is added for the second time and mixed evenly, and the composite oxidant is obtained after drying at 40-45°C.

[0042] The mass ratio of chitosan, aluminum chloride, magnesium oxide and hindered phenolic antioxidant in chitosan sol is 1:4:3:4. The first dosage of hindered phenolic antioxidant is 20% of the total amount of hindered phenolic antioxidant, and the first dosage of hindered phenolic antioxidant is 80% of the total amount of hindered phenolic antioxidant. 25L 1,2-propylene oxide and 2L N,N-dimethylformamide are used for each kilogram of chitosan. The mass ratio of ethanol to water in ethanol aqueous solution is 2:1.

[0043] The preparation method of the sheath is as follows: LDPE particles and HDPE particles are kneaded at 110° C. and a rotation speed of 80 r / min, and after melting, composite antioxidants and flame retardants are added and kneaded for 5 minutes, and then DCP is added and kneaded for 3 minutes, and then the sheath is extruded through a screw extruder to obtain the sheath.

[0044] Embodiment 2: An energy-saving, fire-proof and durable copper alloy wire, comprising a conductor and a sheath. The conductor comprises an inner core and a sheath covering the inner core, the inner core is made of an aluminum alloy rod, and the sheath is made of copper. The conductor is prepared by a coating and stretching process. In terms of weight, the sheath raw material comprises the following components: 98 parts of polyethylene raw material; 3 parts of composite antioxidant; 3 parts of flame retardant; the composite oxidant comprises aluminum oxide-magnesium oxide-composite dry gel, and a hindered phenol antioxidant attached to the aluminum oxide-magnesium oxide-composite dry gel.

[0045] The polyethylene raw materials include LDPE, HDPE and DCP, and the mass ratio of LDPE to HDPE is 20:1. The flame retardants include aluminum hydroxide flame retardant and magnesium hydroxide flame retardant, and the mass ratio of aluminum hydroxide flame retardant to aluminum hydroxide flame retardant is 1:1. The content of DCP in the polyethylene raw material is 1.8phr.

[0046] The preparation method of the composite oxidant is as follows: by weight, 1 part of chitosan is dispersed in 30 parts of deionized water, and then acetic acid solution is added dropwise, and then stirred for 30 minutes to obtain chitosan sol. Aluminum chloride is added to 42 parts of ethanol aqueous solution, and then mixed with chitosan sol, 1,2-propylene oxide, N,N-dimethylformamide, and hindered phenol antioxidant are added for the first time, stirred evenly, and then ultrasonic treatment is performed for 6 minutes. After the sol forms a gel, the formed gel is aged at room temperature and then added to anhydrous ethanol containing magnesium oxide powder, stirred evenly, and then allowed to stand at room temperature for 12 hours. After repeating the stirring and standing steps 5 times, the hindered phenol antioxidant is added for the second time and mixed evenly, and the composite oxidant is obtained after drying at 40-45°C. Among them, the mass ratio of chitosan, aluminum chloride, magnesium oxide, and hindered phenol antioxidant in the chitosan sol is 1:8:6:8. The first dosage of the hindered phenolic antioxidant is 20% of the total amount of the hindered phenolic antioxidant, and the first dosage of the hindered phenolic antioxidant is 80% of the total amount of the hindered phenolic antioxidant. 25L 1,2-propylene oxide and 2L N,N-dimethylformamide are used for each kilogram of chitosan. The mass ratio of ethanol to water in the ethanol aqueous solution is 2:1.

[0047] The preparation method of the sheath is as follows: LDPE particles and HDPE particles are kneaded at 110°C and a rotation speed of 80r / min, and after melting, composite antioxidants and flame retardants are added and kneaded for 10 minutes, and then DCP is added and kneaded for 5 minutes, and then the sheath is extruded through a screw extruder to obtain the sheath.

[0048] Comparative Example 1: A copper alloy wire, comprising a conductor and a sheath. The conductor comprises an inner core and a sheath covering the inner core, wherein the inner core is made of an aluminum alloy rod and the sheath is made of copper. The conductor is prepared by a sheathing stretching process. The sheath raw material comprises the following components by weight: 95 parts of polyethylene raw material; 1 part of hindered phenol antioxidant; and 1 part of flame retardant.

[0049] The polyethylene raw materials include LDPE, HDPE and DCP, and the mass ratio of LDPE to HDPE is 20:1. The flame retardants include aluminum hydroxide flame retardant and magnesium hydroxide flame retardant, and the mass ratio of aluminum hydroxide flame retardant to aluminum hydroxide flame retardant is 1:1. The content of DCP in the polyethylene raw material is 1.8phr.

[0050] The preparation method of the sheath is as follows: LDPE particles and HDPE particles are kneaded at 110°C and a rotation speed of 80r / min, and after melting, hindered phenol antioxidant and flame retardant are added and kneaded for 5 minutes, and then DCP is added and kneaded for 3 minutes, and then the sheath is extruded through a screw extruder to obtain the sheath.

[0051] Comparative Example 2: A copper alloy wire, comprising a conductor and a sheath. The conductor comprises an inner core and a sheath covering the inner core, wherein the inner core is made of an aluminum alloy rod and the sheath is made of copper. The conductor is prepared by a sheathing and stretching process. The sheath raw material comprises the following components by weight: 95 parts of polyethylene raw material; 1 part of composite dry gel; 1 part of flame retardant; and the composite dry gel is aluminum oxide-magnesium oxide-composite dry gel.

[0052] The polyethylene raw materials include LDPE, HDPE and DCP, and the mass ratio of LDPE to HDPE is 20:1. The flame retardants include aluminum hydroxide flame retardant and magnesium hydroxide flame retardant, and the mass ratio of aluminum hydroxide flame retardant to aluminum hydroxide flame retardant is 1:1. The content of DCP in the polyethylene raw material is 1.8phr.

[0053] The preparation method of the composite dry gel is as follows: 1 part of chitosan is dispersed in 30 parts of deionized water by weight, and then acetic acid solution is added dropwise, and then stirred for 20 minutes to obtain chitosan sol. Aluminum chloride is added to 45 parts of ethanol aqueous solution, and then mixed with chitosan sol, 1,2-propylene oxide and N,N-dimethylformamide are added, and ultrasonic treatment is performed for 6 minutes after stirring evenly. After the sol forms a gel, the formed gel is aged at room temperature and then added to anhydrous ethanol containing magnesium oxide powder, stirred evenly, and then allowed to stand at room temperature for 10 hours. After repeating the stirring and standing steps 3 times, the composite oxidant is obtained after drying at 40-45°C.

[0054] The mass ratio of chitosan, aluminum chloride and magnesium oxide in the chitosan sol is 1:4:3. 25L 1,2-propylene oxide and 2L N,N-dimethylformamide are used for each kilogram of chitosan. The mass ratio of ethanol to water in the ethanol aqueous solution is 2:1.

[0055] The preparation method of the sheath is as follows: take LDPE particles and HDPE particles for internal mixing at 110°C and a rotation speed of 80r / min, add composite dry gel and flame retardant after melting and continue mixing for 5 minutes, then add DCP and mix for 3 minutes, and extrude the sheath through a screw extruder.

[0056] Experimental part: 1. Thermal aging test A plurality of samples of the sheath materials of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 were prepared and subjected to heat aging experiments. The heat aging experiment used a heat aging box, the temperature of which was set to 165°C, and the samples were hung on the hanging net in the heat aging box. The samples were taken out of the heat aging box at regular intervals to measure the tensile strength, elongation at break, and crystallinity. The crystallinity was obtained using a differential scanning calorimeter.

[0057] Analysis of elongation at break: From the test results in Table 1, the elongation at break of Example 1 and Example 2 did not change much during the aging period of 0-90h, and decreased to 92% and 88% after aging for 120h, which was a significant decrease. The elongation at break of Comparative Example 1 did not change much during the aging period of 0-60h, and decreased significantly after aging for 90h, which may be due to the decrease in heat aging resistance after the volatilization of the hindered phenolic antioxidant. It can be seen that the alumina-magnesium oxide-composite dry gel in Example 1 and Example 2 effectively restrains the hindered phenolic antioxidant, limits its volatilization, and does not affect the heat aging resistance of the hindered phenolic antioxidant. The elongation at break of Comparative Example 2 changes little during the aging period of 0-30h, and decreases significantly after aging for 60h. This is because the sheath material of Comparative Example 2 does not contain an antioxidant. Combined with the test data of Comparative Example 1, it can be clearly seen that the antioxidant effect in the composite antioxidant is the hindered phenol antioxidant, not the alumina-magnesium oxide-composite dry gel.

[0058] Table 1 Changes of elongation at break with aging time / % Analysis of changes in tensile strength: From the test results in Table 2, the tensile strength of Example 1 and Example 2 changed little during the aging period of 0-90h, and decreased significantly after aging for 120h. The tensile strength of Comparative Example 1 changed little during the aging period of 0-60h, and decreased significantly after aging for 90h. The tensile strength of Comparative Example 2 changed little during the aging period of 0-30h, and decreased significantly after aging for 60h. The change trend of the tensile strength of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 is basically consistent with the change trend of the elongation at break.

[0059] Table 2 Changes of tensile strength with aging time / MPa Analysis of crystallinity change: From the test results in Table 3, the crystallinity of Example 1 and Example 2 changed little during the aging period of 0 to 90 hours, and decreased significantly after aging for 120 hours. The crystallinity of Comparative Example 1 changed little during the aging period of 0 to 60 hours, and decreased significantly after aging for 90 hours. The crystallinity of Comparative Example 2 changed little during the aging period of 0 to 30 hours, and decreased significantly after aging for 60 hours. The crystallinity change trends, tensile strength change trends, and elongation at break change trends of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 are basically consistent.

[0060] Table 3 Changes of crystallinity with heat aging time / % It can be seen from the test results in Tables 1 to 3 that the main antioxidant substance in the composite antioxidant is the hindered phenolic antioxidant. In the absence of alumina-magnesium oxide-composite xerogel, the hindered phenolic antioxidant is easy to volatilize. Alumina-magnesium oxide-composite xerogel can restrain the hindered phenolic antioxidant, limiting the volatilization of the hindered phenolic antioxidant while basically not affecting the hindered phenolic antioxidant's anti-thermal aging effect.

[0061] 2. Environmental stress cracking test The environmental stress cracking test adopts GB / T2951.8-1997, and the sheath samples of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 are prepared. The time when the probability of damage is 50% in an aqueous solution environment with a volume fraction of 10% nonylphenol polyoxyethylene ether is the stress cracking time. The test results are shown in Table 4. There is no cracking under the test conditions of Example 1, Example 2, and Comparative Example 2, and Comparative Example 1 cracks at 40h under the test conditions. After analysis, the sheath raw materials of Example 1, Example 2, and Comparative Example 2 all contain aluminum oxide-magnesium oxide-composite dry gel, while the sheath raw material of Comparative Example 1 does not contain aluminum oxide-magnesium oxide-composite dry gel, indicating that aluminum oxide-magnesium oxide-composite dry gel can effectively improve the environmental stress cracking resistance of polyethylene sheath materials.

[0062] Table 4 Environmental stress cracking test results

Claims

1. An energy-saving, fire-proof and durable copper alloy wire, comprising a conductor and a sheath, characterized in that: The sheath raw material includes the following components by weight: 95-98 parts of polyethylene raw material; 1-3 parts of composite antioxidant; 1-3 parts of flame retardant; the composite oxidant includes aluminum oxide-magnesium oxide-composite dry gel and hindered phenol antioxidant attached to the aluminum oxide-magnesium oxide-composite dry gel.

2. The energy-saving, fire-proof and durable copper alloy wire according to claim 1, characterized in that: The preparation method of the composite oxidant is as follows: aluminum chloride is put into an ethanol aqueous solution, and then mixed with chitosan sol, 1,2-propylene oxide and N,N-dimethylformamide are added, and the mixture is stirred evenly and then subjected to ultrasonic treatment. After the sol forms a gel, the formed gel is aged at room temperature and then put into anhydrous ethanol containing magnesium oxide powder, and stirred evenly and then allowed to stand at room temperature for 10 to 12 hours. After repeating the stirring and standing steps for 3 to 5 times, a hindered phenol antioxidant is added and mixed evenly, and the composite oxidant is obtained after drying at 40 to 45°C.

3. The energy-saving, fire-proof and durable copper alloy wire according to claim 1, characterized in that: In the preparation method of the composite antioxidant, 1,2-propylene oxide and N,N-dimethylformamide are added together with a hindered phenol antioxidant, and then the mixture is stirred evenly and then subjected to ultrasonic treatment for 6 to 8 minutes.

4. The energy-saving, fire-proof and durable copper alloy wire according to claim 2, characterized in that: By weight, 1 part of chitosan was dispersed in 30 parts of deionized water, and then acetic acid solution was added dropwise, and then stirred for 20-30 minutes to obtain chitosan sol.

5. The energy-saving, fire-proof and durable copper alloy wire according to claim 4, characterized in that: The mass ratio of chitosan, aluminum chloride, magnesium oxide and hindered phenol antioxidant in the chitosan sol is 1:4~8:3~6:4~8.

6. The energy-saving, fire-proof and durable copper alloy wire according to claim 2, characterized in that: Polyethylene raw materials include LDPE and HDPE, and the mass ratio of LDPE to HDPE is 20:

1.

7. The energy-saving, fire-proof and durable copper alloy wire according to claim 1, characterized in that: The flame retardant is aluminum hydroxide flame retardant and / or magnesium hydroxide flame retardant.

8. The energy-saving, fire-proof and durable copper alloy wire according to claim 7, characterized in that: The flame retardant includes aluminum hydroxide flame retardant and magnesium hydroxide flame retardant, and the mass ratio of the aluminum hydroxide flame retardant to the aluminum hydroxide flame retardant is 1:

1.

9. The energy-saving, fire-proof and durable copper alloy wire according to claim 1, characterized in that: The preparation method of the sheath is as follows: take LDPE particles and HDPE particles for internal mixing at 110°C and a rotation speed of 80r / min, add composite antioxidants and flame retardants after melting and continue mixing for 5-10 minutes, then add DCP and mix for 3-5 minutes, and extrude the sheath through a screw extruder.

10. The energy-saving, fire-proof and durable copper alloy wire according to claim 1, characterized in that: The conductor comprises an inner core and a covering layer covering the inner core. The inner core is made of an aluminum alloy rod, and the covering layer is made of copper.